Fat-Water Signal-Based Electrical Properties Tomography Using the Dixon Technique - Ren, Yinhao; Yuan, Kecheng; Xu, Guofang; Ye, Chunyou; Liu, Feng; Qiu, Bensheng; Nan, Xiang; Han, Jijun (IEEE transactions on instrumentation and measurement, 2024)
This study aimed to improve the accuracy of electrical properties tomography (EPT) by proposing a fat-water quantification-based EPT (FW-EPT) using the Dixon technique and provided a feasible approach for obtaining electrical properties (EPs) from current clinical routing modalities. Nine human liver-mimicking phantoms were built with varying fat-water (FW) content at 64 MHz. The EPs were measured using the open-ended coaxial probe method, and an FW signal was obtained through Dixon scanning. Subsequently, three sets of fit models were established: F-EPs, considering only fat information; W-EPs, considering only water information; and FW-EPs, considering both fat and water information. To assess the accuracy of these models, FW-EPT experiments were conducted on two healthy subjects, and the results were evaluated using literature values as a reference benchmark. Experiments showed that the FW-EPs fitted model offered the best accuracy. Compared with the literature values, the average relative errors for human liver conductivity and relative permittivity at 1.5T magnetic resonance imaging (MRI) were lower than 2.89% and 5.37%, respectively. The scanning time for clinical human magnetic resonance (MR) experiments was approximately 22 s. FW-EPT enabled faster, higher resolution, and more precise imaging of EPs in human liver tissue. The findings of this study offered new insights for clinical EPT.